2010
DOI: 10.3800/pbr.5.83
|View full text |Cite
|
Sign up to set email alerts
|

A review of genetic intra- and interspecific relationships of deep-sea Buccinum and Neptunea species around Japan (with special reference to the Sea of Japan)

Abstract: Abstract:The Sea of Japan is a marginal sea surrounded by narrow, shallow straits which became isolated from neighboring waters when the sea level fell during the Pleistocene glacial periods. In order to understand the influences of such paleoenvironmental changes on the formation of populations of marine organisms in the Sea of Japan, deep-sea whelks (genera Buccinum and Neptunea (Buccinidae)) are appropriate materials considering their low dispersal abilities through direct development. Deep-sea whelks are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…During the Pleistocene glacial periods in the Sea of Japan, the surface water became brackish, and the bottom water was anoxic (reviewed in Itaki et al 2004). It has been reported that these major environmental changes resulted in reduction of populations of many deep-sea taxa (Kojima et al 2001, Iguchi 2010. As the vertical distribution of both A. lar and A. hozawai is relatively deep (160-260 m; Uji 1994), the two shrimps may have experienced similar demographic responses as a result of environmental changes.…”
mentioning
confidence: 99%
“…During the Pleistocene glacial periods in the Sea of Japan, the surface water became brackish, and the bottom water was anoxic (reviewed in Itaki et al 2004). It has been reported that these major environmental changes resulted in reduction of populations of many deep-sea taxa (Kojima et al 2001, Iguchi 2010. As the vertical distribution of both A. lar and A. hozawai is relatively deep (160-260 m; Uji 1994), the two shrimps may have experienced similar demographic responses as a result of environmental changes.…”
mentioning
confidence: 99%